Viabilidade técnica e econômica da produção de briquetes de lodo do tratamento primário de efluente avícola e serragem - Kunh, Sheila Simone (2022)
This work was carried out with the objective of analyzing the technical feasibility for recycling solid waste from an agro-industry in the West of Paraná through the densification of biomass. The following residues were selected: sludge from the primary treatment of effluents and wood sawdust. The work was divided into two scientific papers: the first investigating the technical feasibility for the production of briquettes as a source of thermal energy, mitigating the risks of current disposal and reducing the operational costs of its destination. To assess the oxidizing characteristics of the briquettes and their mechanical strength, higher calorific value, ash content, volatile materials, fixed carbon, and axial compression strength were evaluated. Thermogravimetric analyzes and differential scanning calorimetry were performed. Statistical treatments were carried out to verify the most significant factors for the production of briquettes, the best proportions of raw materials and to assess whether there is interference from moisture and glue flour used as binder. The briquette that best met the evaluated requirements was a mixture of 15% sludge and 85% sawdust and presented mechanical strength of 23.82 MPa, calorific value of 17.20 MJ/kg and density of 1374.15 kgm-3 . The second paper analyzes the economic and financial feasibility of installing and operating a plant for the production of briquettes from sludge from the primary treatment of effluents and wood sawdust. The initial investment, production costs and economic indicators that proved the economic viability were evaluated, with an Internal Rate of Return of 38.98%, which is higher than the average minimum attractiveness rate of 10%, with a Payback time of 2.98 years and break-even point of 41.10%.